Early Experience With New Generation Deep Brain Stimulation Leads in Parkinson's Disease and Essential Tremor Patients. Issue 4 (21st August 2019) - Shao, Miriam M.; Liss, Andrea; Park, Yunseo L.; DiMarzio, Marisa; Prusik, Julia; Hobson, Ellie; Adam, Octavian; Durphy, Jennifer; Sukul, Vishad; Danisi, Fabio; Feustel, Paul; Slyer, Julia; et al.
Abstract : Background: Newer generation deep brain stimulation (DBS) systems have recently become available in the United States. Data on real‐life experience are limited. We present our initial experience incorporating newer generation DBS with Parkinson's disease (PD) and essential tremor (ET) patients. Newer systems allow for smart energy delivery and more intuitive programming and hardware modifications including constant current and directional segmented contacts. Methods: We compared six‐month outcomes between 42 newer generation and legacy leads implanted in 28 patients. Two cohorts each included 7 PD patients with bilateral subthalamic nucleus (STN) stimulation and 7 ET patients with unilateral ventral intermediate nucleus (VIM) stimulation of the thalamus. All directional leads included 6172 Infinity 8‐Channel Directional leads and Infinity internal pulse generators (Abbott Neuromodulation, Plano, TX, USA) and nondirectional leads included lead 3389 with Activa SC for VIM and PC for STN (Medtronic, Minneapolis, MN, USA). Results: Six‐month outcomes for medication reduction and motor score improvements between new and legacy DBS systems in PD and ET patients were similar. Directionality was employed in 1/3 of patients. Therapeutic window (difference between amplitude when initial symptom relief was obtained and when intolerable side effects appeared with the contact being used) was significantly greater in new DBS systems in both PD ( p = 0.005) and ET ( p = 0.035) patients. The windows for new and legacy systems were 3.60 V ± 0.42 and 2.00 V ± 0.32 for STN and 3.06 V ± 0.44 and 1.85 V ± 0.28 for VIM, respectively. Discussion: The therapeutic window of newer systems, whether or not directionality was used, was significantly greater than that of the legacy system, which suggests increased benefit and programming options. Improvements in hardware and programming interfaces in the newer systems may also contribute to wider therapeutic windows. We expect that as we alter workflow associated with newer technology, more patients will use directionality, and amplitudes will become lower.